A LOW-DOSE LASER (DIODE LASER) APPLICATION REDUCES POCKET PERIODONTAL DEPTH AND CLINICAL ATTACHMENT LOSS - Lessang, Robert; Soeroso, Yuniarti; Juanda, Albert; Kuswandani, Sandra Olivia (International Journal of Applied Pharmaceutics, 2018)
Objective: The initial therapy for chronic periodontitis is scaling and root planing (SRP), followed by non-surgical and surgical therapy. Recently, low-dose laser therapy was mentioned as an adjunctive therapy for periodontitis. This study aims to analyze the effect of degranulation using a low-dose laser (diode laser) after SRP for chronic periodontitis treatment with an attachment loss of â‰¤5 mm compared to SRP alone. Methods: A split-mouth design of in 158 tooth surfaces divided into two groups. The first group was treated with a low-dose laser (diode laser) after SRP, while the second group was treated with SRP only. Bleeding on probing (BOP), probing pocket depth (PPD), and clinical attachment loss (CAL) were all examined at baseline and 35Â days later. Results: The results were statistically significant differences between the two groups were indicated in terms of PPD (p=0.000) and CAL (p=0.040). No significant difference was identified in terms of BOP. Conclusion: The application of a low-dose laser (diode laser) is effective in reducing PPD and CAL as an adjunct therapy in chronic periodontitis treatment.